MEMAKNAI RELEVANSI KONSEP PROFETIK KUNTOWIJOYO DENGAN MANAJEMEN PENDIDIKAN ISLAM - Dartim Dartim (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
This paper discusses how the values of the prophetic spirit coined by Kuntowijoyo can enter certain aspects in the management of Islamic education. This is important because what often happens the concept of management is more focused on administrative matters so that it loses its substantive meaning, namely directed, structured, and character-oriented. This paper is written in the form of scientific articles that refer to scientific books and documents. The result is, that educational management must be focused on the spirit of transcendence which means having a divine dimension, liberation means freeing humans from the shackles of life, and humanization which means being able to synergize goodness towards an organized goal.